PENGARUH HARGA, PRODUK, DAN EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN (Studi Empiris Pada PT. Teh Tambi Wonosobo) - Ahmad Oni Safi’i, 11.05.51.0026 (Students Journal of Economic and Management, 2015)
This study takes an object on the PT. Tambi tea Wonosobo reasons for selecting objects based research because of fluctuations (up and down) the amount of marketing data 2009-2013 . Of the phenomenon it is necessary to evidence and research to analyze the influence , price , product , and experiential marketing on customer loyalty. This type of research is asosiatif. The data used in this research is primary data obtained from questionnaires filled respondents. The population in this study are all customers of PT . Wonosobo Tambi tea with a sample of 100 people by using purposive sampling method. Analysis of the data used in this research is the method of data collection using the questionnaire . The test results showed that (1) the price to customer loyalty showed positive and significant impact, (2) the product to customer loyalty shows a positive and significant influence, (3) experiential marketing on customer loyalty shows a positive and significant effect. Keywords : price, product, experiential marketing, and customer loyalty